New distribution record of the brown sac-wing bat Balantiopteryx infusca in Colombia - Castaño-Salazar, John Harold; Cárdenas-Mosquera, Blas Antonio (Therya Notes, 2020)
The brown sac-wing bat Balantiopteryx infusca (Thomas, 1897) is among the least known of South American bats. Is categorized as Vulnerable by the IUCN, since their description in 1897 was known only to occur in four localities; two from the northwestern Ecuador and two localities from southwestern Colombia. We observed a colony (6 individuals) and collected three adult female specimens in a hollow at c.a. 5 m high at the steep wall of a gorge formed by the Río Gitocito in Corregimiento de Santa Cecilia, municipality of Pueblo Rico, Department of Risaralda, Colombia. The vegetation in this area is dominated by rain forests. The characters that distinguish our vouchers from other Emballonurids, and from other Ballantiopteryx are; glandular sac in the middle of the propatagium; rostrum bulbous anteriorly with lateral inflations extending forward over roots of canines; no sagittal crest; the inner margin of ear slightly concave; braincase elongate posteriorly; mesopterygoid fossa narrow. Our findings represent the northernmost distribution for B. infusca in the Chocó rain forest, extending 170 km north of the nearest record its distribution and filling gaps between known populations of the genus Balantiopteryx. This species endemic to the Chocó region of Colombia and Ecuador tends to be locally rare or hardly detected, more acoustic monitoring should be conducted in the Chocó rain forest to improve the knowledge about the distribution of this bat.